Risk management for the optimal order quantity by risk-averse suppliers of food raw materials - Tyrone T. Lin; Shu-Yen Hsu (International Journal of Financial Studies, 2018)
In uncertain food safety environments, the suppliers of food raw materials (FRM) are facing crucial food safety issues. Therefore, this article aims to probe the risk-averse attitude of FRM suppliers in the face changing marketing environments, in order to establish a decision-making theory as a standard reference for optimization methods to satisfy the maximum expected profit and utility function for the optimal order quantity of FRM suppliers' decision-making. We assume that urgent orders are permitted when products are out of stock, and surplus products will be sold at discounted prices, as based on the food safety circumstances and the differences of market acceptance (optimistic/normal/pessimistic), in order to affect the procurement costs and selling prices. The results of sensitivity analysis for the maximum expected profit show that the probability of imported FRM having no food safety problems when the external environment has no food safety problems is the most important parameter, with the importers fulfilling their responsibility for FRM source quality control. Meanwhile, a responsible attitude toward handling a crisis will reduce losses, transform the crisis into an opportunity, and win the trust of consumers, thereby, fostering corporate sustainability. Sensitivity analysis identifies the significant parameters that influence suppliers' maximum utility function, and provides a reference by which food-related companies may formulate sustainable business policies.
Keywords: 330; risk management; optimal order quantity; risk aversion; food safety